Identifikasi Karakteristik Gejala Serangan Banana Bunchy Top Virus (BBTV) dan Intensitasnya pada Tanaman Pisang di Beberapa Kecamatan di Kabupaten Kutai Kartanegara - Irwansyah Irwansyah; Sofian Sofian; Ni'matuljannah Akhsan (Mulawarman University, 2019)
Banana is one of the fruit commodities that are consumed by many people. Banana dwarf disease is an important disease in Indonesia.This study aims to identify the characteristics of BBTV attack symptoms on banana plants and the physical characteristics of banana plants which are attacked by different planting patterns, sanitation and weed control.This research was carried out in several sub-districts in Kutai Kartanegara District, namely Samboja sub-district, Muara Jawa sub-district, Loa Janan sub-district, Muara Badak sub-district, Loa Kulu sub-district. The method used is the survey method, which is direct observation in the field using a modified score based on the appearance of the sick morphology of the plant (Brooks, 1999).Data obtained from each plot was processed to determine the intensity of each-plot disease using the formula for calculating disease severity (Agrios, 1997). Disease intensity data are compared based on sampling land conditions. Based on the results of a survey conducted at several observation points spread across 5 sub-districts, it can be concluded that the symptom severity is higher in mixed-crop, uses sanitation and weed control compared to monoculture, without sanitation and weed control. The average score of the assessment is a score of 3 with characteristics: (1) the edges of the leaves turn yellow quite severe, (2) the narrowing of the leaves or twisting (3) the occurrence of distortion, dwarf and necrosis (4) found more than four infected banana stems in clump.